JVLA Measurement of Grain Size in the Compact Dust Ring Around Class I Protostar WL 17 - Jun Hashimoto; Hauyu Baobab Liu; Ruobing Dong; Beibei Liu; Takayuki Muto (The Astronomical Journal)
The maximum grain size in protoplanetary disks is a critical parameter for planet formation, as the efficiency of mechanisms like streaming instability and pebble accretion depend on grain size. Even young class 0/I objects, such as HL Tau, show substructures in their disks, indicating the potential for early planet formation. In this study, we investigated the grain size in the dust surrounding the class I object WL 17 using the Karl G. Jansky Very Large Array. Observations were conducted across seven frequency bands ( Q , Ka , K , Ku , X , C , and S bands) ranging from 2 to 48 GHz, corresponding to wavelengths of 15 cm–6.3 mm, with a spatial resolution exceeding 0 $\mathop{.}\limits^{^{′′} }$ 5. While the ring structure at 0 $\mathop{.}\limits^{^{′′} }$ 1 of WL 17 remains unresolved in our data, its emission is clearly detected at all observed frequencies, except at 2 GHz. To estimate the maximum grain size ( ${a}_{{\rm{\max }}}$ ) within the ring, we compared the observed spectral energy distribution (SED) with theoretical SEDs calculated for various ${a}_{{\rm{\max }}}$ values using radiative transfer models. Assuming the dust opacity follows the DSHARP model, our analysis suggests that certain structures internal to the ring achieved a maximum grain size of approximately 4.2 mm. Additionally, we discuss the gravitational stability of the ring and the potential planetary core mass that could form through pebble accretion within the structure.